Treatment of Patients with Early Breast Cancer - Untch, Michael; Banys-Paluchowski, Maggie; Brucker, Sara Y.; Denkert, Carsten; Fasching, Peter A.; Haidinger, Renate; Harbeck, Nadia; Janni, Wolfgang; Krug, David; Loibl, Sibylle; Lüftner, Diana; Michel, Laura; Schumacher-Wulf, Eva; Solbach, Christine; Würstlein, Rachel; Huober, Jens; Ditsch, Nina (Geburtshilfe und Frauenheilkunde, 2025)
This yearʼs 19th St. Gallen (SG) consensus conference on the treatment of patients with early breast cancer (SGBCC: St. Gallen Breast Cancer Conference) is based on numerous patient examples, each with different variables, to reflect the increasingly personalized treatment decision for early breast cancer. More than ever, not only breast cancer subtype, performance status, age and life expectancy are considered as individual factors, but various molecular and genetic variables are also part of the treatment decision. In this manuscript, the SGBCC voting results are discussed by a German group of breast cancer specialists in the context of the recently (2025) updated treatment recommendations of the Commission of the Gynecological Oncology Working Group (AGO Mamma). The German treatment recommendations are based on current evidence. As the international panel of the SGBCC consists of experts from different countries and disciplines, the votes represent an international cross-section of opinions. Therefore, it is useful to discuss the voting results with respect to current German treatment guidelines.Die diesjährige 19. St.-Gallen-(SG-)Konsensus-Konferenz zur Behandlung von Patientinnen mit frühem Mammakarzinom (SGBCC: St. Gallen Breast Cancer Conference) basierte auf zahlreichen fiktiven Fallbeispielen mit jeweils unterschiedlichen Variablen, um der zunehmend personalisierten Therapieentscheidung beim primären – frühen – Mammakarzinom gerecht zu werden. Stärker denn je fließen nicht nur der Mammakarzinom-Subtyp, der Allgemeinzustand und das Lebensalter bzw. die Lebenserwartung als individuelle Faktoren in die Therapieentscheidung ein, sondern auch unterschiedliche molekulare und genetische Variablen. Wie schon in den vergangenen Jahren hat auch dieses Jahr eine deutsche Arbeitsgruppe führender Brustkrebsexpertinnen und -experten die Ergebnisse der internationalen SGBCC 2025 vor dem Hintergrund der deutschen Therapieempfehlungen – speziell der erst kürzlich (2025) aktualisierten Therapieempfehlungen der Kommission Mamma der Arbeitsgemeinschaft Gynäkologische Onkologie e. V. (AGO) – für den Klinikalltag in Deutschland diskutiert. Die deutschen Therapieempfehlungen der AGO Mamma 2025 basieren auf der aktuell vorhandenen Evidenz. Der Abgleich mit dem klinischen Vorgehen in Deutschland bewährt sich seit Jahren, da sich das SGBCC-Panel aus Expertinnen und Experten unterschiedlicher Länder und Fachdisziplinen zusammensetzt, weshalb länderspezifische Besonderheiten in die SGBCC-Empfehlungen einfließen können.
Keywords: St. Gallen Consensus 2025; early breast cancer; genetics; surgery; radiotherapy; (neo)adjuvant systemic therapy; survivorship